2021
DOI: 10.1007/s12325-021-01814-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors for Timely Identification of Possible Occurrence of Delirium in Palliative Care: A Prospective Observational Study

Abstract: Delirium occurs in 50-80% of end-of-life patients but is often misdiagnosed. Identification of clinical factors potentially associated with delirium onset can lead to a correct early diagnosis. To this aim, we conducted a prospective cohort study on patients from an Italian palliative care unit (PCU) admitted in 2018-2019. We evaluated the presence of several clinical factors at patient admission and compared their presence in patients who developed delirium and in those who did not develop it during follow-up… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…First, we observed the importance of the palliative care setting. Our previous publication found that hospice care is associated with a higher risk of developing delirium (HR=2.28, 95% CI 1.45-3.60) as compared to home care [17], while this study, which is not focused on risk factors for delirium but on the role that may have the time to diagnosis on delirium clinical outcomes, highlights a different aspect concerning the setting of care. Among 49 patients with early diagnosis, 46 were managed in hospice and only 3 in a home care program.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…First, we observed the importance of the palliative care setting. Our previous publication found that hospice care is associated with a higher risk of developing delirium (HR=2.28, 95% CI 1.45-3.60) as compared to home care [17], while this study, which is not focused on risk factors for delirium but on the role that may have the time to diagnosis on delirium clinical outcomes, highlights a different aspect concerning the setting of care. Among 49 patients with early diagnosis, 46 were managed in hospice and only 3 in a home care program.…”
Section: Discussioncontrasting
confidence: 59%
“…As already described [17], a total of 503 patients aged 18 or more were enrolled between October 2018 and December 2019 and followed till the date of delirium resolution, death, transfer outside the PCU, patient withdrawal, or end of follow-up (October 28, 2020).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this results in patients being inappropriately treated or untreated (Breitbart & Alici, 2008;Moyer, 2011). It is therefore paramount for clinicians to properly identify the clinical signs of delirium in terminallyill patients and use effective measures of non-pharmacologic and pharmacologic interventions as appropriate to mitigate the distressing problems (Breitbart & Strout, 2000;Corli et al, 2021;Finucane et al, 2020;Hui, 2019). As a dying individual approaches the EOL, treating refractory terminal delirium to mitigate suffering may sometimes require the use of palliative sedation (Arantzamendi et al, 2021;Patel et al, 2019).…”
Section: Terminal Deliriummentioning
confidence: 99%
“…In terminally-ill people, delirium syndrome usually involves multifactorial causes. The most recent evidence from prospective observational studies, systematic reviews and meta-analysis studies report risk factors for terminal delirium to include older age, male sex, organ failure, fluid and electrolyte imbalances, dehydration, suboptimal pain management, hypoxia, breathlessness, poor well-being with declining performance status, and medication adverse effects (Bush et al, 2014; Corli et al, 2021; Ellsworth et al, 2021; Guo et al, 2021). Delirium care poses a significant challenge in EOL care, causing significant distress for the dying person and families, as it is often under-diagnosed or undetected.…”
Section: Clinical Signs and Symptoms That Show Eol Is Imminent In Ind...mentioning
confidence: 99%